Goal programming to model human decision making in ultimatum games - Beullens, Patrick; Zabidi, Nerda Zura; Jones, Dylan F. (John Wiley & Sons, Inc, 2012)
Goal Programming (GP) is applied to modelling the decision making processes in the well-known Ultimatum Game and some of its variations.The decision model for a player is a Chebychev GP model that balances her individual desires with the mental model she has of the desires of other relevant players. Fairness is modelled as a universal mechanism, allowing players to differ in their belief of what a fair solution should be in any particular game. The model's conceptual framework draws upon elements considered of importance in the field of cognitive neuroscience, and results from the field of psychology are used to further specify the types of goals in the model. Computer simulations of the GP models, testing a number of Ultimatum, Dictator and Double-Blind Dictator Games, lead to distributions of proposals made and accepted that correspond reasonably well with experimental findings.